Исследование методов моделирования совместного управления промышленными роботами - Лукьянов, М. С. (ХНУРЭ, 2012)
The given work is devoted to the study of motion simulation of industrial robot manipulators, the joint work of two. Trajectory planning can be performed in the kinematic (if not higher speeds), and in dynamic mode. Thus, there arises the problem of constructing an optimal trajectory plan kinematically redundant manipulator in an arbitrary external environment with unknown location of obstacles in the kinematic regime.
Keywords: промышленные роботы; системы управления; методы моделирования